Beyond perceived ability: the contribution of psychosocial factors to academic performance. Issue 1 (14th September 2016) - Dixson, Dante D.; Worrell, Frank C.; Olszewski‐Kubilius, Paula; Subotnik, Rena F.
Abstract : In this study, we examined the contributions of grit, hope, and academic self‐efficacy to academic achievement in a sample of 609 academically talented students ranging in age from 10 to 18 years. Our hypothesis was that these variables would predict academic achievement above and beyond the contributions of demographic variables and perceived ability. After establishing the reliability and structural validity of scores for the three constructs in this sample, regression analyses indicated that hope and academic self‐efficacy were predictors of perceived ability and that academic self‐efficacy was the most robust predictor of academic achievement. Grit was not a meaningful predictor of either perceived ability or academic achievement. We concluded that psychosocial variables can contribute to performance in talented students, but research is needed to establish which psychosocial variables are the most useful.